1992
DOI: 10.1093/jmedent/29.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Density, and Lyme Disease Spirochete Infection in Ixodes dammini (Acari: Ixodidae) on White-Tailed Deer in Maryland

Abstract: A Statewide survey of ticks parasitizing white-tailed deer was carried out in Maryland during November 1989 to assess the status of the deer tick, Ixodes dammini Spielman, Clifford, Piesman & Corwin, the major vector of Lyme disease in the northeastern United States. Ticks were collected from deer carcasses brought in by hunters at 23 check stations (one per county). A total of 3,437 I. dammini were collected from 538 of 1,281 deer (42%), together with 2,013 Dermacentor albipictus (Packard) and 23 Amblyomma am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
2
9
1
1
Order By: Relevance
“…Nymphs were absent in the northern site in Maine, which is consistent with the absence of tick submissions reported by Rand et al (1991), but not with its classi脼cation as "established" in Penobscot County by Dennis et al (1998). The high density site in Maryland was located in the upper eastern coastal plains, where I. scapularis is well established (Amerasinghe et al 1992, Glass et al 1994, Dennis et al 1998.…”
Section: Discussionsupporting
confidence: 74%
“…Nymphs were absent in the northern site in Maine, which is consistent with the absence of tick submissions reported by Rand et al (1991), but not with its classi脼cation as "established" in Penobscot County by Dennis et al (1998). The high density site in Maryland was located in the upper eastern coastal plains, where I. scapularis is well established (Amerasinghe et al 1992, Glass et al 1994, Dennis et al 1998.…”
Section: Discussionsupporting
confidence: 74%
“…Three species of Ixodid ticks were collected by flagging; I. scapularis, D. variabilis, and A. americanum, yet I. scapularis were the predominate ectoparasites on rodent captures. Previous work by Amerasinghe et al (1992Amerasinghe et al ( , 1993 suggested that lower numbers of I. scapularis ticks collected from flagging and deer sampling studies could explain the reduction of human LD cases along the western Coastal Plains of MD, yet this study suggests that both ticks and mice are infected with B. burgdorferi throughout the study area. Since the risk of human infection is related to exposure to infected ticks (Barbour et al 1993), low incidence of human infection in this region may not be explained by the observed tick and mouse infection levels or the low, overall density of questing ticks, particularly questing nymphal ticks present in this region, although based on the current study the final assertion is more difficult to assess.…”
Section: Discussioncontrasting
confidence: 58%
“…The objective of this study was to determine the infection prevalence of B. burgdorferi in P. leucopus and other potential small animal reservoirs in southern MD where relatively few LD cases are reported annually (I: 6.5 per 100,000 population) (CDC-MMWR 2002) and prevalence of infection among the tick population is moderate (8.2%) (Amerasinghe et al 1992). Our observations indicate that B. burgdorferi s.s. appears to be the only member of this pathogen group circulating in southern MD and that the prevalence of infection in rodents, primarily P. leucopus, is much higher then previously considered.…”
Section: Discussionmentioning
confidence: 99%
“…The overall infection prevalence for B. burgdorferi in adult I. scapularis for this region of 17.6% compares with 8.5% measured in Maryland one decade ago (Amerasinghe et al 1992) and 14.3% in Connecticut from 1989 to 1996 (Stafford III et al 1998). In contrast to the signi脼cant associations identi脼ed between certain environmental factors and tick abundance, no such correlations emerged when those same themes were tested for association with B. burgdorferi-infection in adult I. scapularis.…”
Section: Discussionmentioning
confidence: 66%